BIROKRASI PARTISIPATIF DALAM SEKTOR ENERGI: STUDI KASUS PROGRAM YOUTH ENERGY CONNECT KEMENTERIAN ENERGI DAN SUMBER DAYA MINERAL (ESDM) TAHUN 2025 - Jihan Nur Alifah; Sofia Syahrani; Marsha Nabilla; Anggi Alvionita; Muhammad Prakoso Aji (Jurnal Multidisipliner Bharasumba, 2026)
Energy sector transformation requires a shift in the bureaucratic pattern of the Ministry of Energy and Mineral Resources (ESDM) from a hierarchical model toward a more participatory and collaborative approach. This article analyzes the Youth Energy Connect program as an initiative by the Ministry of ESDM to open public participation spaces in the energy sector. This study uses a qualitative approach with the theoretical framework of Participatory Governance and Collaborative Governance. Data were collected through interviews with informants involved in the program as well as document analysis. The analysis focuses on patterns of interaction between the government and non-state actors in a discussion forum that facilitates the exchange of experiences and perspectives related to energy policy. The findings show that the program has opened a space for discussion that enables direct participation; however, it is still limited in terms of participant inclusivity, program implementation consistency, and mechanisms for follow-up on aspirations. Overall, the program still functions more as a communication space rather than an integrated policy instrument.